2021
DOI: 10.1002/aoc.6550
|View full text |Cite
|
Sign up to set email alerts
|

Organometallic (η6p‐cymene)ruthenium(II) complexes with thiazolyl‐based organic twigs: En route towards targeted delivery via human serum albumin of the potential anticancer agents

Abstract: In this article, we have designed the new ruthenium(II) p‐cymene complexes [Ru(η6‐p‐cymene) HLThz,Me Cl] 1 and [Ru(η6‐p‐cymene) HLThz Cl] 2 with two auxiliary ligand (E)‐1‐(((5‐methylthiazol‐2‐yl)imino)methyl)naphthalen‐2‐ol (HLThz,Me) and (E)‐1‐((thiazol‐2‐ylimino)methyl)naphthalen‐2‐ol (HLThz), keeping in mind the vehicle HSA. The spectroscopic techniques, namely, Fourier transform infrared spectroscopy (FT‐IR), proton nuclear magnetic resonance (1H NMR), 13C NMR, and elemental analysis were employed for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“…Some examples are as follows: Yellol et al [26] have reported the ruthenium arenes complexes of benzimidazole-derived derivatives and studies their cytotoxic potential compared with cisplatin (standard drug); Stepanenko et al [43] reported 3-(1H-benzimidazol-2-yl)-1H-pyrazolo [3,4-b]pyridines derived ruthenium complexes as potential anticancer agents; and Martínez-Alonso et al [44] also reported aryldiazole ruthenium complexes and studied their anticancer properties. In recent years, we have reported several Ru-based organometallic complexes with favorable antitumor properties, [38][39][40][41][42] and we are still striving to develop new Ru-based organometallic compounds that can exhibit better therapeutic efficacy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some examples are as follows: Yellol et al [26] have reported the ruthenium arenes complexes of benzimidazole-derived derivatives and studies their cytotoxic potential compared with cisplatin (standard drug); Stepanenko et al [43] reported 3-(1H-benzimidazol-2-yl)-1H-pyrazolo [3,4-b]pyridines derived ruthenium complexes as potential anticancer agents; and Martínez-Alonso et al [44] also reported aryldiazole ruthenium complexes and studied their anticancer properties. In recent years, we have reported several Ru-based organometallic complexes with favorable antitumor properties, [38][39][40][41][42] and we are still striving to develop new Ru-based organometallic compounds that can exhibit better therapeutic efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…[32] Literature review suggests that benzimidazole-based platinum complexes and their cytotoxicity have been studied extensively to develop new antitumor drugs. [36][37][38][39][40][41][42] On the contrary, studies on the non-platinum-based benzimidazole-derived metal complexes, particularly organometallic compounds, are less explored. Some examples are as follows: Yellol et al [26] have reported the ruthenium arenes complexes of benzimidazole-derived derivatives and studies their cytotoxic potential compared with cisplatin (standard drug); Stepanenko et al [43] reported 3-(1H-benzimidazol-2-yl)-1H-pyrazolo [3,4-b]pyridines derived ruthenium complexes as potential anticancer agents; and Martínez-Alonso et al [44] also reported aryldiazole ruthenium complexes and studied their anticancer properties.…”
Section: Introductionmentioning
confidence: 99%